HIIT and MICT mitigate endothelial dysfunction in early atherosclerotic mice via PCSK9 inhibition - Liu, Guochun; Zhao, Binyi; Chen, Qinglong; Li, Xiang; Zhu, Xuejiao; Duan, Maowei; Zhang, Mengdie; Liu, Zhuohan; Wen, Xuan; Guo, Jia; Zheng, Man; Wang, Ruiyu; et al. (Scientific reports, 2025)
Atherosclerosis (AS), driven by vascular endothelial dysfunction and poses a global health threat. This study compared the therapeutic effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on vascular endothelial function in early-stage AS mice, specifically investigating PCSK9 modulation and the TRX/TXNIP/NLRP3/GSDMD-N pathway. ApoE−/− mice (n = 6/group) fed a high-fat diet for 12 weeks were randomized into sedentary (AS-S), HIIT (AS-HIIT), and MICT (AS-MICT) groups, with wild-type mice as control. Training lasted 12 weeks. Outcomes included body weight, lipid profiles (TG, TC, LDL-C, HDL-C), oxidative stress markers (T-SOD, GSH-Px, MDA), vascular function (eNOS expression, ACh-induced vasorelaxation), and TRX/TXNIP/NLRP3/GSDMD-N pathway activity. Both HIIT and MICT reduced body weight (p < 0.05) and improved lipid profile. Exercise groups showed reduced oxidative stress and inflammation pathways (p < 0.05). HIIT and MICT ameliorate early AS by reducing PCSK9 and oxidative/inflammatory pathway levels (p < 0.05), but HIIT demonstrates superior efficacy in improving endothelial function and pathway activation. These findings show HIIT and MICT mitigate endothelial dysfunction in early atherosclerotic mice via PCSK9 inhibition and advocate for HIIT as a prioritized strategy in early AS management.